Ouers se primêre rol in geloofsvorming - Yates, Hannelie (Verbum et ecclesia, 2025)
Parents’ primary role in faith formation. This article, firstly seeks to explore the role parents play in shaping their children’s faith, and secondly, to examine how it influences congregations’ role. The article begins by providing a concise overview of faith transmission within households as described in the Bible and includes observations about the central role of God in the faith formation process. The article then discusses two significant arguments based on empirical and literature research. The primary argument is that parents hold the most significant influence over their children’s faith formation. This parental role is described by further highlighting four key aspects: (1) setting an example of faith; (2) acting as mentors; (3) fulfilling a socialisation role; and (4) fostering a positive parent-child relationship. The second argument addresses the consequent role of congregations in faith formation. It examines changes in the context, composition, and challenges of contemporary households, highlighting the collaborative role congregations can play in supporting parents in this process. The article concludes by presenting eight paradigm shifts designed to help congregations shape this supportive role effectively. Intradisciplinary/interdisciplinary implications: This article is written from an inclusive youth ministry paradigm, advocating an intentional move away from compartmentalised approaches to ministry and relationships. By adopting a holistic perspective on the role of parents in their children’s faith formation - and, by extension, on the overall well-being of parents and children - it offers valuable insights for congregational studies as well as child, youth, and family studies.